Studi Potensi Heterobeltiosis pada Persilangan Beberapa Galur Cabai Merah (Capsicum annuum L.) - Catur Herison; , Rustikawati; , Sudarsono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
Hybrid cultivar is one of the best alternative to increase national hot pepper production. However, lacking of local hybrid cultivars resulted in the dependency on imported expensive seeds. The objective of this research is to study heterobeltiosis potential and yield of hybrids generated from crosses of several hot pepper lines. Nine parental lines and their 19 hybrids were evaluated in field experiment at the Pasir Sarongge Experimetal Station of IPB, Cipanas, West Java, in a randomize complete block design with 3 replications. The results indicated that several crosses showed a high potential heterobeltiosis. The cross of CI034 x CI026, CI042 x CI025, dan CI042 x CI026 showed heterobeltiosis value of more than 100%. Most of the crosses revealed an excellent yield for medium fruit type the yield was about 1 kg per plant (CI034 x CIO06), and for large fruit type was 1,8 kg per plant (CI042 x CIO06), in average, which were higher than the yield of Hot Beauty, a commercial hybrid cultivar. Key words: Heterobeltiosis, Hot pepper